Evaluation of lysozyme as potential alternative for replacement of antibiotic as feed supplement for growth performance in broiler birds - FUKE, A.R.; KADAM, M.M.; BHAISARE, D.B.; PATIL, A.R.; ROKADE, J. J.; RANVIR, A.B. (Indian Journal of Poultry Science, 2025)
An experiment was conducted on 360 broiler chicks to study the impact of lysozyme as potential alternative for replacement of antibiotic as feed supplement for growth performance. The day old chicks were distributed in six treatment groups on similar body weight basis with three replicates in each. The birds under control group received basal diet. The two treatment groups received basal diet supplemented with antibiotic flavomycin @ 100 g/ton of feed and lysozyme @ 250 g/ton of feed. One treatment group was challenged with Clostridium Perfringens on 17, 18 and 19th day of age without any supplementation. Remaining two groups were challenged with Clostridium Perfringens with the supplementation of antibiotic flavomycin @ 100 g/ton and lysozyme @ 250 g/ton of feed. At the end of the experiment, the feed intake and feed conversion ratio, body weight of broiler chicken were significantly (P<0.05) improved due to addition of dietary lysozyme compared to non- supplemented control group birds. The non-supplemented but Clostridium perfringens challenged birds showed significantly lower body weight gain compared to treatment group supplemented with lysozyme. Intestinal microbiology assays shows that supplementation of lysozyme and antibiotic gives more beneficial effect on gut bacterial count at early age, whereas the age of the bird progress the effect nullified. In can be concluded that addition of Lysozyme (@ 250 gm per Ton of feed) can be good alternative for antibiotic in commercial broiler diet for higher live body weight, gut health and overall performance without affecting performance of broiler birds.